Porphyromonas gingivalis laboratory strains and clinical isolates exhibit different distribution of cell surface and secreted gingipains - Seers, Christine A. (J Oral Microbiol, 2020)
Background: The cell-surface cysteine proteinases RgpA, RgpB (Arg-gingipain), and Kgp (Lys-gingipain) are major virulence factors of P. gingivalis, a keystone pathogen in the development of destructive periodontal disease. The gingipains function as proteinases and transpeptidases utilising small peptides such as glycylglycine as acceptor molecules. However, the characteristics of the gingipains from most P. gingivalis strains have not been determined. Methods: We determined the phenotypes of a panel of P. gingivalis laboratory strains and global clinical isolates with respect to growth on blood agar plus whole-cell and vesicle-free culture supernatant (VFSN) Arg- and Lys-specific proteinase activities. Results: The P. gingivalis isolates exhibited different growth characteristics and hydrolysis of haemoglobin in solid media. Whole-cell Arg-gingipain Vmax varied 5.8-fold and the whole cell Lys-gingipain V(max) varied 2.1-fold across the strains. Furthermore, the P. gingivalis strains showed more than 107-fold variance in soluble Arg-gingipain activity in VFSN and more than 371-fold variance in soluble Lys-gingipain activity in VFSN. Glycylglycine and cysteine stimulated Arg- and Lys-specific cleavage activities of all strains. The stimulation by cysteine was in addition to its redox effect consistent with both glycylglycine and cysteine promoting transpeptidation. Conclusion: The global P. gingivalis clinical isolates exhibit different Arg- and Lys‑gingipain activities with substantial variability in the level of soluble proteinases released into the environment.